Radio-sensitivity of irradiated seed, plantlets, callus, and in vitro leaves from Indigofera zollingeriana Miq by gamma rays. Issue 1 (November 2021) - Royani, J I; Sudarsono; Abdullah, L; Aisyah, S I
Abstract: Test of radio-sensitivity is important to use as a recognizable effect of radiation. The optimal doses usually create maximum variability. Radio-sensitivity of each part of plants of Indigofera zollingeriana Miq to gamma rays had no report yet. This research aimed to know radio-sensitivity, optimal doses, and growth of M1 generation from each material of I. zollingeriana irradiated with gamma rays. Seed, plantlets, callus, and in vitro leaves were tested for radio sensitivity by gamma rays. Doses level used of Gamma rays were: 0 until 500 Gy. The value of LD50 of each material was evaluated using Curve-fit Analysis. Growth parameters from each material were observed for six weeks after planting and analyzed using IBM SPSS 22. Research showed that the sensitivity of each doses level was different for each source of the material plant. The seed had radio-sensitivity of gamma rays at dose 183.988 Gy, plantlet at dose 253.677 Gy, callus could not calculate, and in vitro leaves at dose 242.241 Gy.